Stigma, obesity, and the health of the nation's children. [article]. - Puhl, Rebecca M.
Preventing childhood obesity has become a top priority in efforts to improve our nation's public health. Although much research is needed to address this health crisis, it is important to approach childhood obesity with an understanding of the social stigma that obese youths face, which is pervasive and can have serious consequences for emotional and physical health. This report reviews existing research on weight stigma in children and adolescents, with attention to the nature and extent of weight bias toward obese youths and to the primary sources of stigma in their lives, including peers, educators, and parents. The authors also examine the literature on psychosocial and physical health consequences of childhood obesity to illustrate the role that weight stigma may play in mediating negative health outcomes. The authors then review stigma-reduction efforts that have been tested to improve attitudes toward obese children, and they highlight complex questions about the role of weight bias in childhood obesity prevention. With these literatures assembled, areas of research are outlined to guide efforts on weight stigma in youths, with an emphasis on the importance of studying the effect of weight stigma on physical health outcomes and identifying effective interventions to improve attitudes. -- (from the author)